The utilisation of Antarctic microalgae isolated from Paradise Bay (Antarctic Peninsula) in the bioremediation of diesel - Zamree, Nur Diyanah; Puasa, Nurul Aini; Lim, Zheng Syuen; Wong, Chiew-Yen; Shaharuddin, Noor Azmi; Zakaria, Nur Nadhirah; Merican, Faradina; Convey, Peter; Ahmad, Syahida; Shaari, Hasrizal; Azmi, Alyza Azzura; Ahmad, Siti Aqlima; et al. (Multidisciplinary Digital Publishing Institute, 2023)
Research has confirmed that the utilisation of Antarctic microorganisms, such as bacteria, yeasts and fungi, in the bioremediation of diesel may provide practical alternative approaches. However, to date there has been very little attention towards Antarctic microalgae as potential hydrocarbon degraders. Therefore, this study focused on the utilisation of an Antarctic microalga in the bioremediation of diesel. The studied microalgal strain was originally obtained from a freshwater ecosystem in Paradise Bay, western Antarctic Peninsula. When analysed in systems with and without aeration, this microalgal strain achieved a higher growth rate under aeration. To maintain the growth of this microalga optimally, a conventional one-factor-at a-time (OFAT) analysis was also conducted. Based on the optimized parameters, algal growth and diesel degradation performance was highest at pH 7.5 with 0.5 mg/L NaCl concentration and 0.5 g/L of NaNO3 as a nitrogen source. This currently unidentified microalga flourished in the presence of diesel, with maximum algal cell numbers on day 7 of incubation in the presence of 1% v/v diesel. Chlorophyll a, b and carotenoid contents of the culture were greatest on day 9 of incubation. The diesel degradation achieved was 64.5% of the original concentration after 9 days. Gas chromatography analysis showed the complete mineralisation of C7–C13 hydrocarbon chains. Fourier transform infrared spectroscopy analysis confirmed that strain WCY_AQ5_3 fully degraded the hydrocarbon with bioabsorption of the products. Morphological and molecular analyses suggested that this spherical, single-celled green microalga was a member of the genus Micractinium. The data obtained confirm that this microalga is a suitable candidate for further research into the degradation of diesel in Antarctica.